Polymorphism of IL-17A Gene (Rs2275913), In Obese and Smokers of Covid-19 Patients in Wasit Province, Iraq - Abbood , Dhoha Hamzah; Hussein , Asyad Abdul-Abbas; Salih , Alyaa Abdulhadi; Jaleel, Isra'a; Jasim, Noor Aziz (American Journal of Biology and Natural Sciences, 2024)
Severe COVID-19 disease was linked to a severe proinflammatory response and cytokine storm interleukin 17 (IL-17) is one of these cytokines, was associated with severe acute lung injury and multiorgan dysfunction. Single nucleotide polymorphisms (SNPs) in genes coding IL-17 can affect level of IL-17 hence its role in diseases. Various host factors associated with an increased risk of disease such as; older age, obesity and smoking, led to increased risk of getting severe COVID-19. Aim of study to determine SNPs of the IL-17A gene at rs2275913 (G > A) are associated with COVID-19, in groups of smokers and obese covid-19 patients . So this study included 24 obese COVID-19 patients, 25 smokers with COVID-19, 25 non-obese & non-smoking COVID-19 patients (as control positive) and 21 healthy people (as negative control). Genotyping of the IL-17A (rs227591) SNP in studied groups was performed by the ARMS-PCR technique. Results of the analysis shown no statistical difference between IL17A (rs2275913) genotypes or alleles in relation to the different studied groups. While the genotypic and allelic frequencies observed in all samples studied, the A allele (1.1 %), G allele (16.8%), and AG genotype (82.1 % ), test of homogeneity showed that were significantly different in all samples regarding the genotypic and allelic frequencies. The heterozygous AG genotype of IL17A ( rs2275913) was have the highest frequency among the different studied groups, also there was noticeable prevalence of the homozygous GG genotype, While the prevalence of the homozygous AA genotype it's almost non-existent. Thus, the different genotypes of IL-17A G/A-rs 2275913 can be proposed as markers of the severity of COVID-19 infections and risk factors (Smoking and Obesity).